Growth, Expansion of Markets, and Income Elasticities in World Trade - Wu, Yi (IMF Working Papers; Working Paper ;, 2005)
The Houthakker-Magee effect implies that a country facing unfavorable income elasticities in trade must either grow at a slower rate than its trading partners or experience a trend worsening of its current account and/or depreciation of its real exchange rate. Krugman (1989) first documented the existence of a '45-degree rule' under which relative income elasticities are systematically related to relative growth rates. In this paper, we develop and test an intertemporal current account model in which Krugman's original 45-degree rule is a special case. The result suggests that secular trends in current accounts and/or real exchange rates are much smaller than one would have projected based on conventional income elasticities.